PENGARUH OPINION SHOPPING, DISCLOSURE DAN REPUTASI KAP PADA OPINI AUDIT GOING CONCERN - Kusumayanti, Ni Putu Evi; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2017)
Auditors have a responsibility to give due consideration to the company's survival. The phenomenon occurs when the liquidation of some companies that obtain an unqualified opinion but went bankrupt the following year. This can happen because the manipulation of accounting in an entity which lead to errors giving opinions by the auditor to companies experiencing financial distress. The purpose of this study is to determine the influence of opinion shopping, disclosure and reputation of KAP on going concern audit opinion in Indonesia Stock Exchange period 2011-2015. The method used in this research is non probability sampling with purposive sampling technique. Data obtained from the research method is 115 companies. Data analysis technique used is the logistic regression analysis. The analysis finds that the opinion shopping, disclosure and reputation of KAP has effect going concern audit opinion.
Keywords: going concern audit opinion, opinion shopping, disclosure and reputation of KAP